2019
DOI: 10.1142/s021798491950026x
|View full text |Cite
|
Sign up to set email alerts
|

Coexisting attractors, circuit realization and impulsive synchronization of a new four-dimensional chaotic system

Abstract: This paper presents a new four-dimensional chaotic system with three nonlinearities and two equilibria. The most striking feature of the new system is that it has different types of asymmetric coexisting attractors. Simulation experiments are used to study the complex dynamic behaviors of the system. The chaos, period-doubling bifurcation, coexisting attractors with respect to system parameters and initial values are found in the system. It shows that the system has coexisting chaotic attractors, coexisting pe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 32 publications
0
8
0
Order By: Relevance
“…As b increases in [12,20], the bifurcation diagrams clearly show the trajectory of system (1) from classical period-doubling bifurcation to chaos. Table 1 shows the comparison of the Lyapunov exponents of the new system with the literature [12,[28][29][30]. It can be seen that the maximum LE 1 of the new system is larger.…”
Section: Bifurcation Diagrams Lyapunov Exponents and Period-doublinmentioning
confidence: 93%
See 1 more Smart Citation
“…As b increases in [12,20], the bifurcation diagrams clearly show the trajectory of system (1) from classical period-doubling bifurcation to chaos. Table 1 shows the comparison of the Lyapunov exponents of the new system with the literature [12,[28][29][30]. It can be seen that the maximum LE 1 of the new system is larger.…”
Section: Bifurcation Diagrams Lyapunov Exponents and Period-doublinmentioning
confidence: 93%
“…In 2017, Lai et al proposed a unique 4D autonomous system with a signum function term [29], which can generate various types of coexisting attractors. In 2019, Zhou et al proposed a chaotic system with multiple asymmetric coexisting attractors [30] and carried out circuit simulation and pulse synchronization research.…”
Section: Introductionmentioning
confidence: 99%
“…Step-size (h) Error h = 1.0 0.5017 h = 0.1 0.0070 h = 0.01 0.0021 h = 0.001 0.0020 Figure 1: Numerical results for Caputo fractional problem (2) showing the comparison between the exact and approximate (numerical) results for t = 10. Take note of the variation in the amplitudes.…”
Section: Test Problem Consider the Following Caputo Fractional Differential Equationmentioning
confidence: 99%
“…Studies have shown that the classic Lorenz and Rössler systems will generates coexisting attractors for some parameter regions [16], [17]. Some simple chaotic systems are also found to have coexisting attractors [18]- [24]. Some effective methods were put forward to construct an arbitrary number of coexisting attractors from simple chaotic systems [25], [26].…”
Section: And Yangmentioning
confidence: 99%